Investigating lubrication properties using pulse-echo ultrasound technique - Imad F.; Nagi F.; Ahmed S.K. (IEEE Computer Society, 2023)
This paper presents a technique that utilizes ultrasonic puls-echo method to determine insufficient lubrication in static mechanical components and assemblies. Due to prolong static in-operation of such systems as spring actuated circuit breakers (CB) the lubricants/grease in the actuation mechanism dries up resulting in sluggish response. Since these systems remain static they don't emit any acoustic signals. Therefore active pulse-echo ultrasonic testing method is proposed to determine the lubricant condition. In the proposed method wavelet analysis is used to de-noise the signal and extract data about lubricant condition. The extracted features from different samples is be used to develop a fuzzy inference system to define the lubricant condition. 2012 IEEE.